Hong Kong stock listing and the sensitivity of managerial compensation to firm performance in state-controlled chinese firms - Ke, Bin (2013)
We compare the sensitivity of managerial cash compensation to firm performance, the level of long term managerial incentives, and the sensitivity of CEO turnover to firm performance for three types of state-controlled Chinese firms: A shares (firms incorporated and listed in mainland China), H shares (firms incorporated in mainland China but listed in Hong Kong), and Red Chip shares (firms incorporated outside mainland China and listed in Hong Kong). We find no difference in the three pay-for-performance sensitivity measures between H shares and A shares. The cash pay-for-performance sensitivity and the level of long-term managerial incentives are higher for Red Chip shares than for the other two firm types. However, the sensitivity of CEO turnover to firm performance is insignificant for all three firm types. Our study illustrates the complexity in the influence of mainland China’s versus Hong Kong’s institutional forces on state-controlled Chinese firms listed in Hong Kong.